การตรวจติดตาม Escherichia coli และ Listeria monocytogenes ที่ถูกกระทำด้วยไนซินและเซทิลไพริดิเนียมคลอไรด์โดยเทคนิค Atomic force microscopy และ Raman spectroscopy - ฉัตรนภา อินทานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Nisin and cetylpyridinium (CPC) have been used as antimicrobial agents to against wide variety of bacteria for food preservation. The objective of this study was to use Atomic force microscopy (AFM) and Raman spectroscopy to investigate the antimicrobial agents localization and morphological changes that occurred in L. monocytogenes and E. coli cells treated with nisin and CPC. The minimal inhibitory concentration (MIC) by microtiter plate assay, of nisin and CPC against L. monocytogenes was found to be 125 IU/mL and 0.75 µg/mL, respectively. The MIC against E. coli was  30,000 IU/mL and 3.175 µg/mL, respectively. Both separately and in combination showed that indifference. However, AFM examination revealed severely injured cells when L. monocytogenes and E. coli were exposed to a combination of nisin and CPC. The Raman peak signal of CPC (1652 cm-1) and nisin (3090 cm-1) were observed on bacterial cell membrane (2934 cm-1) after E. coli cells were exposed to a combination of nisin and CPC. The Raman mapping demonstrated the detailed information of antimicrobial agent composition that were localized and randomly distributed on bacterial cell membrane. In conclusion, AFM and Raman spectrometer were effective tools for investigating antimicrobial activity on bacterial cells and could be useful tools for studying antimicrobial effects of biochemical compound especially for food preservation.